DIGITAL DIPLOMACY AND BUSINESS STRATEGY FOR THE REVITALIZING REGIONAL ECONOMIC AT PHILIPPINES IN ERA 4.0 - Indah Kusumawati; Sugeng Siswondo; Abdul Rosid (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
The condition of the Covid-19 pandemic has paralyzed almost all aspects of people's live. It also has an impact on the economic industry, especially in the Special Capital Region of Manila Philippines. Therefore, this condition needs special attention to rise the economic life of the community, especially in the economic industry, revitalization of the economic sector in the new normal era. This study aimed to explain the strategy of revitalizing regional economies from the perspective of digital diplomacy, in which digital technology was used as a means of digital reformation in realizing smart economic conditions for regional economic revitalization strategies from the perspective of the strategy government. using quantitave methods with SPSS version 25 tools, with the research location in philiphiness , using 100 responden using validity test, realibility tests, and regression analysis. Results of digital diplomacy results for the strategy business has positive prediction (0.821) and digital diplomacy for the economic sector 0.799 business strategy for the economic sector 0.740.